2009
DOI: 10.1016/j.ejcts.2008.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Progressive right ventricular failure is not explained by myocardial ischemia in a pig model of right ventricular pressure overload

Abstract: We conclude that in our model RV failure during PAC develops in spite of increased coronary blood flow and MVO(2). Thus, mechanisms different from ischemia may contribute to progressive RV failure after pulmonary embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…Underlining this, Kohlhardt et al described already in the 1960s a significant, moderateacidosisinduced cardiac output decrease in nonfailing cats by 25% (pH = 7.00) (13). Further investigations on acidosis-induced decrease of myocardial contractility and its effect on catecholamine response were performed using different approaches and models (14)(15)(16)(17)(18)(19)(20)(21)(22); however, there still exist no experimental data describing the specific effect of metabolic acidosis in isolated ovine hearts even though sheep are widely used as animal models (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…Underlining this, Kohlhardt et al described already in the 1960s a significant, moderateacidosisinduced cardiac output decrease in nonfailing cats by 25% (pH = 7.00) (13). Further investigations on acidosis-induced decrease of myocardial contractility and its effect on catecholamine response were performed using different approaches and models (14)(15)(16)(17)(18)(19)(20)(21)(22); however, there still exist no experimental data describing the specific effect of metabolic acidosis in isolated ovine hearts even though sheep are widely used as animal models (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…We and others have shown that RV contractile dysfunction from acute RVPO can occur in the absence of detectable ischemia (3,16,17), and we previously reported that desmin, troponin-I, and spectrin (proteins that are reportedly degraded in some models of experimental ischemia/reperfusion) (18)(19)(20)(21)(22)(23)(24) are not degraded in our model of acute RVPO (7). In that study (7), we considered the possibility that we might have failed to detect the degradation of these proteins because of the relatively short period of RVPO.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the inability to maintain the cardiac index and arterial pressure leads to cardiogenic shock (fig. 3) [15,16]. Thus, RV dysfunction is the critical hemodynamic event and an important determinant of the clinical presentation, course and prognosis of PE.…”
Section: Pathophysiology Of Right Ventricular Dysfunction and Failurementioning
confidence: 99%